2011
DOI: 10.1021/ja109706y
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Magnet Behavior for an Antiferromagnetically Superexchange-Coupled Dinuclear Dysprosium(III) Complex

Abstract: A family of five dinuclear lanthanide complexes has been synthesized with general formula [Ln(III)(2)(valdien)(2)(NO(3))(2)] where (H(2)valdien = N1,N3-bis(3-methoxysalicylidene)diethylenetriamine) and Ln(III) = Eu(III)1, Gd(III)2, Tb(III)3, Dy(III)4, and Ho(III)5. The magnetic investigations reveal that 4 exhibits single-molecule magnet (SMM) behavior with an anisotropic barrier U(eff) = 76 K. The step-like features in the hysteresis loops observed for 4 reveal an antiferromagnetic exchange coupling between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
288
3
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(312 citation statements)
references
References 64 publications
20
288
3
1
Order By: Relevance
“…In all the three cases, the χ M T product decreases slightly between 300 and~50 K, before a more rapid decrease below~30 K, to reach values of 4.24(3), 9.52(4) and 11.02(5) cm 3 ·K·mol −1 at 2.0 K. For such Ln III ions with an unquenched orbital moment associated with a ligand field, the decrease of the χ M T product as the temperature is lowered can originate from the following possible contributions [50]: (a) the thermal depopulation of the Stark sublevels; (b) the presence of magnetic anisotropy; and (c) antiferromagnetic interactions between the Ln III centers. The relatively low χ M T values at 2.0 K may suggest the contribution of a weak to moderate Ln III ···Ln III interaction (Ln = Tb, Dy, Ho), as confirmed for the Gd III 2 complex 2.…”
Section: Magnetic Susceptibility Studiesmentioning
confidence: 98%
See 1 more Smart Citation
“…In all the three cases, the χ M T product decreases slightly between 300 and~50 K, before a more rapid decrease below~30 K, to reach values of 4.24(3), 9.52(4) and 11.02(5) cm 3 ·K·mol −1 at 2.0 K. For such Ln III ions with an unquenched orbital moment associated with a ligand field, the decrease of the χ M T product as the temperature is lowered can originate from the following possible contributions [50]: (a) the thermal depopulation of the Stark sublevels; (b) the presence of magnetic anisotropy; and (c) antiferromagnetic interactions between the Ln III centers. The relatively low χ M T values at 2.0 K may suggest the contribution of a weak to moderate Ln III ···Ln III interaction (Ln = Tb, Dy, Ho), as confirmed for the Gd III 2 complex 2.…”
Section: Magnetic Susceptibility Studiesmentioning
confidence: 98%
“…As expected for pure Ln III systems, the exchange interaction is rather weak as a consequence of the shielded 4f orbitals that have small overlap with bridging ligand orbitals. This J value is typical for dinuclear complexes containing the {Gd III 2(μ2-OR)2} 4+ core [17,18,20,25,50]. Rov and Hughbanks performed a spin density functional (SDFT) study of dinuclear Gd III complexes containing the {Gd2(μ2-OR)2} 4+ core [20].…”
Section: Magnetic Susceptibility Studiesmentioning
confidence: 99%
“…5), but to simulate the low temperature w M T(T) and M(H) data, we need to account for a weak exchange interaction. One way to simulate such thermodynamic data for orbitally degenerate ions is the Lines model 27 , which employs an isotropic exchange between the spin component of the angular momenta (S ¼ 5 / 2 for Dy(III); see Methods) and has been used previously to model interactions between lanthanides 15,28 . Employing this model with PHI 29 we find J Lines ¼ þ 0.047(1) cm À 1 , which gives excellent fits to both w M T(T) and M(H) (Fig.…”
Section: Synthesismentioning
confidence: 99%
“…Radical bridging ligands can provide a strong magnetic exchange pathway between two lanthanide ions, leading to magnetic hysteresis at 14 K 3,4 . In other compounds weak Ln Á Á Á Ln interactions can shift the zero-field quantum tunnelling step to a finite field, known as exchange biasing 15 , with different effects on cryogenic magnetization curves depending on the sign of the exchange 16,17 or even mask single-ion slow relaxation modes 18 . More frequently, however, Ln Á Á Á Ln interactions increase quantum tunnelling rates, leading to apparently lower U eff values when compared with paramagnetic Ln ions doped into a diamagnetic lattice 8,17,19 .…”
mentioning
confidence: 99%
“…Previous investigations have observed that exchange coupling can enhance SMM behavior in Ln complexes. 12,[32][33][34][35][36] Exchange coupling in Cp* 2 Yb(bipy) (3)…”
Section: Exchange Coupling In Lanthanide Single Molecule Magnets (1)mentioning
confidence: 99%